The Creative Commons is Starving: Calling for a Universal Basic Income - Sorbara, Joe (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Improvising drummer and community organizer Joe Sorbara advocates for the implementation of a Universal Basic Income (UBI) that will “provide everyone with the space to hear and recognise a calling, and . . . ensure that we all have the capacity and support to answer the call.”